The Revised Charter and Ordinances of the City of Detroit 150 (1848) - (:unkn) unknown (My University, 1848)
§§ 9-10: No person shall fire or set off any squib, cracker, gunpowder or fire works, or fire any gun or pistol in any part of this city, unless by written permission of the Mayor or two Aldermen, which permission shall limit the time of such firing, and shall be subject to be revoked at any time by the Common Council; and any person or persons violating any of the provisions of this section, shall forfeit the penalty of five dollars for each and every offence. § 10. Every person firing a cannon within this city, unless by permission of the Mayor or two Aldermen, shall forfeit the penalty of twenty-five dollars: Provided, that nothing in this or the preceding section shall be construed to prohibit any military company from firing any gun or cannon when authorized by their commanding officer or officers.
Keywords: DISCHARGE